THE STUDY OF THE TECHNICAL PLAN OF POST MINES LAND LIMESTONE QUARRY IN PT SEMEN BATURAJA (PERSERO) TBK - Afif Rahman; Restu Juniah; Maulana Yusuf (Indonesian Journal of Environmental Management and Sustainability, 2018)
Limestone mining activities of PT Semen Baturaja Ogan Komering Ulu Regency Tbk South Sumatra Province is done in the open mining quarry mining mining with the system. Limestone is the primary raw material required in the manufacture of cement in PT semen baturaja Tbk. Mining activities in the quarry is open at the end of its activities, will leave the land mines. Land mines must be utilized in order to make the environment mining can function returns appropriate allocation. Utilization of land mines can be done for a variety of Evergreen plants such as designation, orchards, and others. Designation ex limestone mines of PT Semen Baturaja Tbk as contained in document his rope Post Plans, one of which is for Evergreen plants. Research conducted in the survey aims to assess, technically land use limestone mines of PT Semen Baturaja for Evergreen plants so that land mines can be used again, so that the negative effects of mining activities can be reduced. The results showed, the utilization of land of a former limestone to plant pine PT Semen baturaja has met the required technical aspect in planning post-war mine . Research results are expected to be of benefit to the stakeholders, academics, researchers, practitioners and the Association of mining, and the environment. Keywords: land use Plan, a former Post-war mines, technical aspects, Plant Evergreen